Peranan Tari Pagar Pengantin Dalam Pesta Pernikahan Masyarakat Di Bayung Lencir - Silviana Silviana; Afifah Asriati; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2019)
Research using descriptive methods. The research instrument was the researchers herself and assisted with supporting instruments such as stationeries, photo camera and DSLR camera. The types of data in this study were primary and secondary data. The techniques of data collection were observation, interview, and documentation. In analyzing This article aimed to find out the Role of Pagar Pengantin Dance in the Environment of the Bayung Lincir District. The type of this research was qualitative the data, there were several stages, namely, data reduction and data presentation. The results showed that the Pagar Pengantin dance in the Bayung Lencir district was only performed at weddings. Pagar Pengantin dance performed at weddings had a role as a release of single age. As related to the appearance of, the bride must join in as a dancer and dance with four bride fence dancers. This dance must be pulled in front of the aisle seat because this dance must be witnessed by the groom who aimed to protect the dancing bride. Married brides are no longer permitted to dance except with permission from their husbands because the symbols from the trays used by the bride's stand are likened to houses where married women have restrictions. Pagar Pengantin Dance is a dance that means separation between the bride and her family to form a new family, and this dance also symbolizes the meaning of the union of two different families into one.